Influence of Highway Traffic on Contamination of Roadside Soil with Heavy Metals - Benabid Abderrahmane; Benmbarek Naima; Mansouri Tarek; Merdas Abdelghani (Civil Engineering Journal, 2021)
This study is one of the first works which examined the assessment of heavy metal contamination of pavement-side soils in Algeria. It deals with the section of National Highway 3 (RN3), which crosses the wilaya of Batna. In the environment of sampling sites there is no industry or dangerous activity on the environment, the heavy metals addressed in this study are (Pb, Cu, Cr, Fe, Ni, Zn), their origin being road traffic. The objectives of this study were to: (1) Determine the concentrations of heavy metals in road dust; (2) Identify the sources of different heavy metals in soils and road dust; (3) Exploring the extent of heavy metal pollution in neighbouring soils. To this end, 33 samples were collected, including 03 road dust and 30 soil samples over different distances from 1m to 80m. The samples were analyzed by FRX. Results indicated that concentrations in road dust were higher than in soil. The distribution of heavy metal concentrations in dust is Fe>Pb>Zn>Cu>Cr>Ni, and the distribution in the ground is Fe>Pb>Cu>Zn>Cr>Ni in the direction of Biskra and in the opposite direction and decreases away from the road, while the distribution in the central solid ground is Fe> Cu>Cr>Pb>Zn>Ni. Climatic conditions such as wind, rainfall, temperature, humidity and the nature of the terrain were also significantly related to their enrichment in these roadside soils. The enrichment factor (EF) and the geo-accumulation index (Igeo) were calculated, as well as all elements with a (EF) that ranges from moderate to high to extremely contaminated, reflecting the high anthropogenic load of these metals in the study area and the results of the Igéo accumulation indices confirm the results obtained for the enrichment factor (EF). Doi: 10.28991/cej-2021-03091736 Full Text: PDF